Evaluation of Mycobacterium avium subsp. paratuberculosis isocitrate lyase (IcL) and ABC transporter (BacA) knockout mutants as vaccine candidates - Eshraghisamani, Razieh; Arrazuria, Rakel; Luo, Lucy; De Buck, Jeroen (Frontiers in Cellular and Infection Microbiology, 2023)
There has been little success in controlling Johne’s disease, caused by Mycobacterium avium subsp. paratuberculosis, due to suboptimal diagnostics and the ineffectiveness of available vaccines. By knocking out BacA and IcL, genes required for MAP survival in dairy calves, two live-attenuated vaccine candidates were created. This study evaluated the host-specific attenuation of MAP IcL and BacA mutants in mouse and calf models, as well as the elicited immune responses. Deletion mutants were generated in MAP strain A1-157 through specialized transduction and found viable in vitro. First, the mutants’ attenuation and elicited cytokine secretion were assessed in a mouse model, 3 weeks after intraperitoneal inoculation with MAP strains. Later, vaccine strains were assessed in a natural host infection model where calves received 109CFU oral dose of MAP wild-type or mutant strains at 2 weeks old. Transcription levels of cytokines in PBMCs were evaluated at 12-, 14-, and 16-weeks post-inoculation (WPI) and MAP colonization in tissue was assessed at 4.5 months after inoculation. Whereas both vaccine candidates colonized mouse tissues similarly to wild-type strain, both failed to persist in calf tissues. In either mouse or calf models, gene deletion did not reduce immunogenicity. Instead, inoculation with ΔBacA induced a greater upregulation of proinflammatory cytokines than ΔIcL and wild-type in both models and a greater expansion of cytotoxic and memory T-cells than uninfected control in calves. ΔBacA and wild-type strains significantly increased secretion of IP-10, MIG, TNFα, and RANTES in mice serum compared to uninfected control. This agreed with upregulation of IL-12, IL-17, and TNFα in calves inoculated with ΔBacA at all time points. The ΔBacA also gave rise to greater populations of CD4+CD45RO+, and CD8+ cells than uninfected control calves at 16 WPI. Low survival rate of MAP in macrophages co-incubated with PBMCs isolated from the ΔBacA group indicated that these cell populations are capable of killing MAP. Overall, the immune response elicited by ΔBacA is stronger compared to ΔIcL and it is maintained over two different models and over time in calves. Further investigation is warranted to evaluate the BacA mutant's protection against MAP infection as a live attenuated vaccine candidate.